(untitled) (Papeles, 2022)
Considering legal–criminal dogmatics as a permanent struggle to develop concepts in a global and unique system of Criminal Law, in the present study, the different perspectives regarding mens rea are presented in a brief analysis, showing how it is possible to determine whether a person involved in a criminal offense has acted – or omitted to act- willfully.